Religion in public life : a dilemma for democracy - Thiemann, Ronald F. (Georgetown University Press, 1996)
Prayer in public schools, abortion, gay and lesbian rights - these bitterly divisive issues dominate American politics today, revealing deep disagreements over basic moral values. In a highly readable account that draws on legal arguments, political theory, and philosophy, Ronald F. Thiemann explores the proper role of religious convictions in American public life. He proposes that religion can and should play an active, positive part in our society even as it maintains a fundamental commitment to pluralist, democratic values.